2014
DOI: 10.1093/jmcb/mju038
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots of DNA double-strand breaks and genomic contacts of human rDNA units are involved in epigenetic regulation

Abstract: DNA double-strand breaks (DSBs) are involved in many cellular mechanisms, including replication, transcription, and genome rearrangements. The recent observation that hot spots of DSBs in human chromosomes delimit DNA domains that possess coordinately expressed genes suggests a strong relationship between the organization of transcription patterns and hot spots of DSBs. In this study, we performed mapping of hot spots of DSBs in a human 43-kb ribosomal DNA (rDNA) repeated unit. We observed that rDNA units corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 56 publications
9
76
1
Order By: Relevance
“…Moreover, an additional locus of 35S rDNA was present after MH treatment in barley cells, which suggests that either a duplication or double strand breaks (DBS) occurred within the 35S rDNA locus. Though the NOR regions were found to exhibit increased fragility both in some plants [44, 45] and in humans [46], we did not observe this in Brachypodium cells. A different sensitivity of 5S rDNA and 25S rDNA sequences was also reported in C .…”
Section: Resultscontrasting
confidence: 84%
“…Moreover, an additional locus of 35S rDNA was present after MH treatment in barley cells, which suggests that either a duplication or double strand breaks (DBS) occurred within the 35S rDNA locus. Though the NOR regions were found to exhibit increased fragility both in some plants [44, 45] and in humans [46], we did not observe this in Brachypodium cells. A different sensitivity of 5S rDNA and 25S rDNA sequences was also reported in C .…”
Section: Resultscontrasting
confidence: 84%
“…Based on lasso regression, we found that the CTCF motif had the highest beta coefficient (β = 3.22), corresponding to OR = 25 (Fig. 7c), supporting recent evidence showing that long-range contacts are involved in DNA repair [25,35,41]. Furthermore, motifs of tumor proteins p53, p63, and p73 had high coefficients (β > 2.03, OR > 7.6), in agreement with previous predictions based on To assess the significance of those motifs, we built a logistic regression model without any regularization including all motifs with β > 0.5.…”
Section: Prediction From Dna Motifs and Shapesupporting
confidence: 85%
“…8; Smerdon 1991). In support of this model, open chromatin and the epigenetic marks found at TAD boundaries (e.g., H3K4me3 and CTCF) have been linked to chromatin fragility in human disease (De and Michor 2011;Tchurikov et al 2015), species evolution (Carbone et al 2009a;Lemaitre et al 2009), and simulation analyses (Berthelot et al 2015). Moreover, an in vitro study recently showed that chromosome loop anchors bound by CTCF and cohesin are vulnerable to DSBs mediated by topoisomerase 2B (TOP2B) and act as fragile sites for chromosomal rearrangements (Canela et al 2017).…”
Section: Gibbon Breakpoints Overlap Boundaries Of Tadsmentioning
confidence: 88%